This is the day your life must surely change: Prioritising behavioural change in musculoskeletal practice. (September 2021) - Lewis, Jeremy; Ridehalgh, Colette; Moore, Ann; Hall, Kevin
Abstract: Behavioural change is the modification or transformation of behaviour. Health behaviour has been defined as, 'any activity undertaken for the purpose of preventing or detecting disease or for improving health and wellbeing' (Bennell et al ., 2019 [1]). For a smoker it is acting on the decision to stop or reduce the number of cigarettes smoked, for someone with a higher than ideal body mass index, it is acting to reduce weight and for someone who isn't achieving ideal levels of exercise (Briggs et al ., 2020 [2]) it is the decision and action to increase metabolic activity. With increased understanding of the importance of self-management and impact of lifestyle, clinicians supporting people presenting with musculoskeletal symptoms have recognized that behavioural change is an essential component of the care we need to prioritize. It is about sharing the benefits of lifestyle choices that promote health, discussing how to introduce and maintain them, and supporting people through their journey of change, so the change becomes the new normal. Behavioural change science assumes that (i) morbidity and mortality are due in part to certain behaviours and (ii) these behaviours are modifiable. The aim of this debate article is to discuss reasons why clinicians must include long term behavioural change into their management plan and methods they may use to facilitate the change ensuring recipients are empowered to act and make today the day their 'lives will surely change'.